The effectiveness of realization of regional innovative policy: problems and ways of development - Bekniyazova, D.S.; Kashuk, L.I.; Davidenko, L.M.; Stecenko, I.P. (BUKETOV BUSINESS REVIEW, 2020)
Object: assessment of the effectiveness of regional economic policy implementation in the Republic of Kazakhstan, which allows to assess the General trends and features of regional development, their advantages and disadvantages for achieving their economic stability and development. Methods: During the research, rationing of indicators based on traditional linear scaling was used to obtain relative data, on the basis of which regional ratings for all estimated indicators for 2013–2017 were determine. Results: The need for innovative development of the economy of Kazakhstan has actualized issues related to the efficiency of the national economy and factors affecting it, and therefore it is analyzed the dynamics of the main macroeconomic indicators in the country in recent years. The assessment of the level of development of regions on the basis of macroeconomic indicators was carried out in order to determine functional tasks, the solution of which is most important for regional development. Conclusions: In general, it is emphasized that the socio-economic development of the regions has a significant impact on the quality of life and well-being of the population, as well as on the development of the economic potential of the region and its innovative and investment attractiveness, which generally affects the country’s welfare.